Sources of variance in exposure to nonneutral trunk postures in varying working situations - van der Beek, Allard J.; Kuiper, Judith I.; Dawson, M.; Burdorf, Alex; Bongers, Paulien M.; Frings-Dresen, Monique HW (Scandinavian Journal of Work, Environment & Health, 1995)
' ' OBJECTIVES ': 'The purpose of this study was to estimate the different components of variance in exposure to nonneutral trunk postures. Methods For the primary measures analyses of variance were used to determine the percentage of worktime spent in trunk flexion and trunk rotation or lateroflexion during 10-min observation periods. For two occupational groups six observation periods were selected per worker, and for four other groups 10 periods were used. Most of the 35 subjects were not restricted to one workplace, and they performed dynamic work while being observed. Results The variance within workers contributed around 80% to the total variability of exposure to both unfavorable postures. These results indicate that it is difficult to achieve an unbiased estimate of exposure to postural stress for individual workers who perform dynamic tasks in varying work situations. Conclusions measurement strategy for exposure assessment requires many repeated observations per worke
Keywords: back pain; exposure assessment; lumbar posture; measurement strategy; misclassification; observation; occupational epidemiology; variability